Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan melalui Penggunaan Metode Simulasi pada Murid Kelas V Sekolah Dasar 277 Sarecoppeng Kecamatan Lilirilau Kabupaten Soppeng - Andi Sugiati; Jumiati Nur (JED (Jurnal Etika Demokrasi), 2017)
The main problem of the study is the low learning outcomes of Civics in grade V SD Negeri 277 Sarecoppeng District Lilirilau Soppeng District. By it, applied simulation method in learning. This research is a Classroom Action Research that aims to improve the learning outcomes of Civics in grade V SD Negeri 277 Sarecoppeng Kecamatan Lilirilau Soppeng District through the application of simulation methods. Subjects in this classroom action research are grade V students of SD Negeri 277 Sarecoppeng with a total of 12 students consisting of 4 men and 8 women. This research was conducted in 2 (two) cycles. Data collection is done by using observation and test in the form of descriptions carried out at each cycle. The data collected were analyzed by using descriptive analysis both quantitatively and qualitatively. After the learning through the application of simulation method for two cycles. Students who previously lacked enthusiasm in following the learning process became more active. The average score of test results from each cycle can be seen in the first cycle with an average score of 70.00 is in the high category. And in cycle II with an average score of 85.00 is in very high category. From this research shows that the application of methods can improve the learning outcomes of Civics in grade V SD Negeri 277 Sarecoppeng Lilirilau District.Keywords: Learning Outcomes, Simulation Methods, students.